Radiological Clinical Practice Guidelines Published in the Last Decade: A Bibliometric Analysis - Hong, Su Jin (J Belg Soc Radiol, 2019)
OBJECTIVES: To provide a comprehensive review of radiological clinical practice guidelines (CPGs) and to establish their characteristics and impact in the field of radiology. MATERIAL AND METHODS: A MEDLINE search was performed for CPGs in which at least half of the authors were from the radiology or imaging department. The following information was extracted from each CPG: year of publication, journal, provider, number of authors, number of pages, number of references, collaboration, country of origin, radiological subspecialty, imaging modality used, topic, source of funding, and number and pattern of citations. RESULTS: In total, 120 radiological CPGs published between July 2006 and June 2016 were identified. One hundred nine (90.8%) radiological CPGs were published in radiology journals, 96 (80.0%) were provided by the scientific community, 108 (90.0%) were collaborative studies, 64 (53.3%) originated from the United States, 36 (30.0%) were concerned with the field of vascular/interventional radiology, 38 (31.7%) used combined imaging techniques, 52 (43.3%) were focused on interpretation and management, and 118 (98.4%) were not funded. Radiological CPGs included a median of 8 authors, 9 pages, and 49 references. The median number of citations and annual citations were 18 (range, 0–540) and 3.5 (range, 0–75.6), respectively. CONCLUSION: Our study presents several interesting insights into the characteristics and impact of radiological CPGs.